Land Use and Land Cover Transitions in Shirdi-Impacts on Pilgrimage and Urban Development - Dr. Sharad Ambadas Borude,; Mr. Sampat Chandrakant Dhokane, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Shirdi, an important pilgrimage site in India, attracts devotees from around the country and the world, fostering faith in Saibaba. Over the past three decades, Shirdi has undergone significant changes in land use and land cover due to increased tourism and rapid urbanization. This transformation is associated with the growth of tourist infrastructure, including hotels, commercial establishments, roads, parking facilities, transportation terminals, and residential complexes. To gain a better understanding of this phenomenon, a study was conducted analyzing the land use and land cover transition within a 5 km buffer radius of Shirdi. The study spanned four decades from 1991 to 2021, focusing on a 30-year period. The findings of the study indicate a rapid increase in built-up areas within the study area. This research emphasizes the importance of comprehensive planning and sustainable development strategies to mitigate the negative impacts of land use changes in Shirdi. By comprehending these transitions and their consequences, policy makers and stakeholders can collaborate to ensure the preservation of Shirdi's natural resources and cultural heritage while catering to the needs of the growing pilgrimage industry.
Keywords: Pilgrimage; Land Use; Land Cover; Transitions